Development of problem solving ability test on the work-energy material - John Rafafy Batlolona; Wartono Wartono; Sutopo Sutopo; Desella Inna Rahmatina (Intelektual Pustaka Media Utama, 2019)
The purpose of this research is to develop test questions of problem solving ability on work-energy material for high school students class X. This type of research is research and development. The model used in this study is ADDIE with the stages of analyzing, planning, developing, implementing, and evaluating, but this study only up to the implementation stage. The test developed in this research consists of three items of problem solving ability description that is multi context. Validation of item was done by content validation and empirical validation. The results of content validation indicate that the average score of test items is 3,125 with good category. The results of empirical validation indicate that there are two valid questions and one invalid question. Two valid questions have a Cronbach Alpha coefficient of 0.807. The results of the implementation of the test showed that the average student problem solving abilities in Question 1 is 17.41 of a maximum score of 25, the lowest score is 10 and the highest is 23. The results of students in the question number 2 by 16.60 of a maximum score of 25, with the lowest score is 10 and the highest is 22. These results indicate that the test instrument is feasible to use to assess students' problem solving abilities.